PERANCANGAN TABUNG REAKTOR DESTILASI MICROWAVE-ASSISTED HYDRO DISTILLATION SKALA INDUSTRI RUMAHAN - Sabdha Purna Yudha; Dwi Setyorini; Achmad Qodim Syafaatullah (Otopro, 2025)
This study presents an innovative design of a reactor vessel for Microwave-Assisted Hydro Distillation (MAHD), optimized for household-scale essential oil production. MAHD, as an energy-efficient alternative to conventional distillation methods, was applied through a newly designed reactor that emphasizes heat transfer optimization and energy efficiency. The reactor was constructed from stainless steel 304 with a capacity of 30–50 liters, integrated with a microwave heating system (500–2000 W), and equipped with a copper pipe condenser. Experimental results demonstrated an increase in essential oil yield of up to 30% compared to conventional hydrodistillation, with extraction times significantly reduced (reaching 100 °C in less than 15 minutes at 1000 W). Further analysis identified optimal operating conditions at 450 W with a feed-to-solvent (F/S) ratio of 0.35 g/mL. This design provides a significant solution for enhancing the efficiency of essential oil production in household industries, with potential implications for reducing energy consumption and improving product quality.